Aplikasi Pengelolaan Persediaan Barang Toko Bintang Jaya Berbasis Android - Dedy Haryanto; Kristina; Amok Darmianto (LPPM Universitas Widya Dharma Pontianak, 2025)
In today's digital era, effective inventory management is essential to ensure smooth business operations and meet customer demands. The system is designed to facilitate stock monitoring, real-time inventory updates, allowing store owners to manage inventory more efficiently. This study aims to design an Android-based inventory management information system for Toko Bintang Jaya in Simpang Hilir District. The methods used in this study include object-oriented analysis and design techniques, with system modeling using Unified Modeling Language (UML). The system analysis process involves mapping user needs, designing workflow diagrams, and identifying features that will be implemented in the system. The application was developed using android studio as the main text editor, with the Java programming language. For database management, use Firebase Realtime Database, which allows the system to store and access data in real-time. In addition, this system also uses the concept of NoSQL for more flexible and efficient data management in Android-based applications. The results of this study are expected to increase efficiency and accuracy in inventory management, minimize stock recording errors, and improve the quality of service to customers. With the implementation of this system, inventory management will become faster and more reliable, thereby reducing the risk of excess or shortage of stock. Overall, this research contributes to the development of information technology in the retail sector and supports businesses in optimizing inventory management processes.